(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
Some general aspects of the systematics and nomenclature of the Acari are discussed, such as the great number of papers published every year, the problem of badly known species, the contact between specialists, the International Code of Zoological Nomenclature, the grouping of genera and species. Some additional notes are given with reference to recent publications on various groups, e.g. the Mesostigmata, the Tetranychidae, the epizootic mites, the Eriophyidae, the Acaridiae, and the Oribatei.